2019
DOI: 10.1002/slct.201803291
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Functional Group Characterization of Fulvic Acid from Hami Lignite

Abstract: This research investigates the extraction of fulvic acid (FA) from Hami lignite from Xinjiang, China, by microwave-hydrogen peroxide and microwave-hydrogen peroxide-formic acid methods. The effects of reaction time, oxidant concentration, oxygen-coal ratio and microwave power on FA yield are determined. Sulfuric acid-acetone was applied to purify the primary FA products. The results indicate that the oxidant concentration is a sensitive factor affecting the yield of FA, while reaction time has little effect. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Zhumanova et al 20 reported that sulfuric acid promote the conversion of carbon (C) in coal to a greater extent without increasing the loss of nitrogen (N) and oxygen (O). In addition, by applying hydrogen peroxide (H 2 O 2 ), potassium permanganate (KMnO 4 ) and nitric acid (HNO 3 ), coal oxidation can change the carbon chain structure of HAs and increase the number of active functional groups, such as hydroxyl and carboxyl 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhumanova et al 20 reported that sulfuric acid promote the conversion of carbon (C) in coal to a greater extent without increasing the loss of nitrogen (N) and oxygen (O). In addition, by applying hydrogen peroxide (H 2 O 2 ), potassium permanganate (KMnO 4 ) and nitric acid (HNO 3 ), coal oxidation can change the carbon chain structure of HAs and increase the number of active functional groups, such as hydroxyl and carboxyl 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Under the optimum conditions, the extraction yield of FA was ~80‰. The extraction yield of FA in this paper is basically the same as that catalytic oxidation with hydrogen peroxide 46,47 . Compared with the traditional FA extraction process, the citric acid–ethanol method is environmentally friendly.…”
Section: Discussionmentioning
confidence: 82%
“…The extraction yield of FA in this paper is basically the same as that catalytic oxidation with hydrogen peroxide. 46,47 Compared with the traditional FA extraction process, the citric acid-ethanol method is environmentally friendly. Characterization and analysis of the extracted and purified FA revealed that the molecular structure of FA hardly changed before and after purification and that there were many oxygen-containing functionalitiessuch as carboxyl, phenolic hydroxyl, and alcohol hydroxyl groupsin the structure, which are beneficial to the growth and development of plants.…”
Section: Discussionmentioning
confidence: 99%
“… 1 3 As a thermal processing conversion method, the pyrolysis of lignite is one effective way to efficiently utilize lignite, as the processing conditions are mild, the operation is simple, and the products are retrievable. 4 6 …”
Section: Introductionmentioning
confidence: 99%